2001
DOI: 10.2337/diabetes.50.1.175
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I mRNA and Signaling in the Diabetic Retina

Abstract: IGF-I promotes the survival of multiple cell types by activating the IGF-I receptor (IGF-IR), which signals downstream to a serine/threonine kinase termed Akt. Because in diabetes vascular and neural cells of the retina undergo accelerated apoptosis, we examined IGF-I synthesis and signaling in the human and rat diabetic retina. In retinas obtained postmortem from six donors aged 64 ± 8 years with a diabetes duration of 7 ± 5 years, IGF-I mRNA levels were threefold lower than in the retinas of six age-matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…Blood was obtained by cardiac puncture for the measurement of GHb (Glyc-Affin GHb assay; PerkinElmer, Norton, OH). From each animal, one eye was fixed in 10% buffered formalin at room temperature for the preparation of retinal wholemounts or sections, and the contralateral retina was isolated under the dissecting microscope and either homogenized for protein studies (14) or weighed and extracted in 6% ice-cold perchloric acid to measure sorbitol and fructose content. The measurements of retinal sorbitol and fructose were performed by the laboratory of Dr. Peter Oates at Pfizer using fluorometric enzyme assays (15,16).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood was obtained by cardiac puncture for the measurement of GHb (Glyc-Affin GHb assay; PerkinElmer, Norton, OH). From each animal, one eye was fixed in 10% buffered formalin at room temperature for the preparation of retinal wholemounts or sections, and the contralateral retina was isolated under the dissecting microscope and either homogenized for protein studies (14) or weighed and extracted in 6% ice-cold perchloric acid to measure sorbitol and fructose content. The measurements of retinal sorbitol and fructose were performed by the laboratory of Dr. Peter Oates at Pfizer using fluorometric enzyme assays (15,16).…”
Section: Methodsmentioning
confidence: 99%
“…The retinas were homogenized in ice-cold lysis buffer (14), and the proteins were resolved by electrophoresis on 12% SDS-PAGE and electroblotted. The blots were probed with the GFAP antibodies (1:40,000), and immunoreactive bands were detected and quantitated as previously described (14). The results are expressed as densitometric units per microgram of protein.…”
Section: Methodsmentioning
confidence: 99%
“…However, baseline Akt phosphorylation of serine-473, although not of threonine-308, and Akt activity (as determined by in vitro assay) showed reductions in STZ-diabetic rats (Laviola et al, 2001). Gerhardinger and coworkers (Gerhardinger et al, 2001) found that STZ-diabetic rats given low-dose insulin treatment tended to exhibit enhanced retinal Akt phosphorylation. We found that in STZ-diabetic rats, short-term insulin treatment can ameliorate endothelial dysfunction by inducing overexpressions of eNOS and/or VEGF mRNAs, possibly via IGF-1 receptors (Kobayashi and Kamata, 2002a).…”
Section: Pi3-k/akt Pathway and Endothelial Dysfunction In Type I Diabmentioning
confidence: 99%
“…To capture the earliest effects of diabetes on the retinal vessels and the impact of TGF-b inhibition, we profiled gene expression in rats with 3.5 months of diabetes, a duration insufficient to cause histopathology 16 or even to accelerate apoptosis 18 in rat retinal vessels. A group of diabetic rats and a group of control rats received SM16 for 3 weeks; the drug did not affect body weight, blood glucose, or the levels of HbA 1c (Table 1).…”
Section: Diabetes and Sm16 Synergistically Alter Gene Expression In Rmentioning
confidence: 99%
“…The RNA was reverse-transcribed into cDNA, as previously described. 18 Gene-expression profiling was performed using the RT 2 Profiler Endothelial Cell Biology PCR Array (PARN-015; SABiosciences/Qiagen). The array plates included a panel of housekeeping genes used for normalizing the PCR array data, and the appropriate controls for genomic DNA contamination, RNA quality, and PCR performance.…”
Section: Pcr Array and Real-time Pcrmentioning
confidence: 99%